A STUDY ON STUDENTS’ ATTITUDE IN LEARNING ENGLISH AS A FOREIGN LANGUAGE IN TWO CLASSES OF (A&H) FAST AND SLOW LEARNERS AT SMP NEGERI 01 MANOKWARI - Pratama, Laurensius Dian; Sukristiningsih, Sukristiningsih (Universitas Papua Manokwari, 2016)
The study entitled “a study on students’ attitude in learning English as a foreign language in two classes at Sekolah Menengah PertamaNegeri 01, Manokwari” presents the attitude of highest ability of class (8A) and lowest ability of class (8H). This research is partof a case study Attitude of this study is considered as one of important role in deciding positive and negative toward particularlearning, in this term is EFL. It is also divided into three components which are called affective, behavior and cognitive. Aswe know that students in junior high school are special group of age that create rapid transition of changes, their attitudescan be vary, especially the foreign language they learn. The method that is used in this study is the cross sectional methodwhich is part of survey research design according to Creswell (2012).The results of this study show that students in class 8A mostly tend to have Normal category based on the questionnaires.Meanwhile for the class 8H, the results show that positive attitudes are mostly found based on the questionnaires. However,for the results of behavior observation, changes happen in context of the learning activity within English classroom. The class8A has more positive behavior toward English subject rather than class 8h. The class 8H did not present whether positiveor negative behavior, only for undecided/normal behavior rose within English learning process.